Hedge Funds, Systemic Risk, and Dodd-Frank The Road Ahead - Dixon, Lloyd (RAND Corporation, 2013)
These proceedings summarize the key themes and issues raised during a September 2012 RAND symposium. Discussion focused on how hedge funds might contribute to systemic risk and the extent to which recent financial reforms address these risks.